Object-oriented Design Framework for Stock Keeping Unit Generating System (Jurnal Teknologi (Sciences & Engineering), 2013)
This paper proposes an object-oriented design for generating Stock Keeping Unit coding system. Through recognition and analysis of the inventory item particulars and conceptualizing the important classes as one package, the framework is developed in a modular-basis able to be integrated with other parts of the system. Using UML class and package diagram as of the best practice in object-oriented, conducting the analysis and design is elaborately discussed. A prototype implementation is carried out to support the designed framework over its applicability at a modular information system. Moreover, the item particular package with unique and organized SKU numbering system efficiently supports the fundamental need of item identification at inventory control operations and classification and guarantees different types of reports and lookups.